Scientific evidence underlying contraindications to the ketogenic diet: An update. (10th July 2020) - Watanabe, Mikiko; Tuccinardi, Dario; Ernesti, Ilaria; Basciani, Sabrina; Mariani, Stefania; Genco, Alfredo; Manfrini, Silvia; Lubrano, Carla; Gnessi, Lucio
Summary: First identified as a feasible treatment for intractable epilepsy, the ketogenic diet (KD) has recently gained popularity thanks to growing evidence on applications such as weight loss, most importantly, but also NAFLD, cancer, neurologic conditions and chronic pain. As with any treatment, whether pharmacologic or not, the KD might not be an appropriate intervention for every individual, and a number of contraindications have been proposed, now deeply rooted into clinical practice, excluding de facto many patients that could benefit from its use. However, many of these concerns were expressed due to the absence of clinical studies conducted on fragile populations, and an assessment of lately emerged evidence relative to KD safety is currently lacking and much needed. We herein provide a critical revision of the literature behind each safety alert, in order to guide through the treatment options in the case of subjects with an indication to the KD and a borderline safe situation. Based on available evidence, the possible use of this diet as a therapeutic intervention should be assessed on a patient‐to‐patient basis by adequately skilled medical doctors, keeping in mind current recommendations, but reading them through the knowledge of the current state of the art.